2009
DOI: 10.1002/jhm.494
|View full text |Cite
|
Sign up to set email alerts
|

Improving insulin ordering safely: The development of an inpatient glycemic control program

Abstract: This report describes a Glycemic Control Program instituted at an academic regional level-one trauma center. Key interventions included: 1) development of a subcutaneous insulin physician order set, 2) use of a real-time data report to identify patients with out-of-range glucoses, and 3) implementation of a clinical intervention team. Over four years 18,087 patients admitted to non-critical care wards met our criteria as dysglycemic patients. In this population, glycemic control interventions were associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…Eleven studies met the inclusion criteria for our review [21][22][23][24][25][26][27][28][29][30][31]. After excluding duplicates, we screened titles and abstracts of 1110 articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies met the inclusion criteria for our review [21][22][23][24][25][26][27][28][29][30][31]. After excluding duplicates, we screened titles and abstracts of 1110 articles.…”
Section: Resultsmentioning
confidence: 99%
“…Full texts of 62 articles meeting the criteria or of uncertain nature were obtained. Eleven studies met the inclusion criteria for our review [21][22][23][24][25][26][27][28][29][30][31]. Another three articles meeting the inclusion criteria were identified through the secondary search [32][33][34] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies evaluating this intervention showed positive results, with reductions in both hypoglycemia and hyperglycemia rates [111, 120122]. One study showed no significant improvements in glycemic control with the use of a “multi-component intervention that included an out-of-range glucose report derived electronically” [123]. The financial impact of glucose dashboards for health systems has not been formally studied.…”
Section: Evidence-based Intervention Programs Across the Population Hmentioning
confidence: 99%
“…Order sets have successfully increased the provision of underused interventions such as venous thromboembolism pharmacoprophylaxis (VTEP), 1,2 basal insulin therapy, 3,4 and aggressive fluid resuscitation for sepsis; 5,6 many of these have been modularized and merged into comprehensive order sets 1 in the context of quality improvement initiatives. Quality improvement initiatives have the potential for unintended consequences.…”
Section: Introductionmentioning
confidence: 99%